(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. Effective economic development of the enterprise, satisfaction of social needs of its employees and filling the state budget depends first of all on the ability of the enterprises to receive income from their activities. The purpose of the article is to analyse the influence of various factors on the gross profit of an industrial enterprise on the basis of deterministic models that are grounded on financial statements, using statistical methods and approaches. Results. The amount of profit is affected by the various interdependent factors that influence the enterprise performance both in positive and negative ways. Factor analysis is performed to determine the quantitative impact of each of these factors. Factor analysis provides a comprehensive and systematic investigation of these factors and measurement of their influence on the key performance indicators. The article considers the application of the deterministic multiplicative models of the gross profit on the example of an industrial enterprise. The model contains four factors: average annual cost of the fixed assets (quantitative factor), the share of the active part of fixed assets in the total cost of the fixed assets, return on active fixed assets, gross profit margin (qualitative factor). The multiplicative index models of gross profit were built for the enterprise for 2016-2019. Absolute and relative changes in gross profit due to the changes in factors of the model were calculated by two methods: the method of chain substitutions and the method of detecting an isolated impact of a factor. To increase gross profit at the enterprise certain reserves were revealed such as improvement of structure of the fixed assets through increasing the share of machinery and equipment, increase in the efficiency of their use due to the growth of return on active part of fixed assets and increase in gross profit margin due to the growth of volume of sales as well as decrease in cost of goods sold. Conclusiоns. The deterministic multiplicative models of gross profit of the industrial enterprise, that were built for 2016-2019 years by the method of chain substitutions and the method of detecting an isolated impact of a factor, showed shortcomings in determining the contribution of all the factors except quantitative (volumetric) by the first method, and more accurate results for the second one. Therefore, it is recommended to apply more actively in practice the method of detecting the isolated influence of factors.